2023
DOI: 10.1088/1748-9326/acb563
|View full text |Cite
|
Sign up to set email alerts
|

Human influence on historical heaviest precipitation events in the Yangtze River Valley

Abstract: With the recurrence of high-impact extreme weather and climate events and the growing demands by the public to know the causes after the events, event attribution has emerged as a frontier of climate change research. Typically, an event attribution study focuses on one individual extreme event that has just occurred. Studies rarely examine human influence on multiple extreme events in different times of the past. Here we conduct a comprehensive attribution analysis on a number of the heaviest precipitation eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Meanwhile, Z. Wang et al. (2023) analyzed four extreme Meiyu precipitation events that occurred in MLYR in 1931, 1954, 1998, and 2020, and their conclusions partially corroborate our findings. The competitive effects of GHG and AA forcings make it challenging to detect the signal of human activities in very heavy precipitation days, as these signals can be intermingled with natural variability effects.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Meanwhile, Z. Wang et al. (2023) analyzed four extreme Meiyu precipitation events that occurred in MLYR in 1931, 1954, 1998, and 2020, and their conclusions partially corroborate our findings. The competitive effects of GHG and AA forcings make it challenging to detect the signal of human activities in very heavy precipitation days, as these signals can be intermingled with natural variability effects.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…The precipitation seasonality is important to agricultural production, vegetation growth, ecological and socio-economic development [16][17][18]. The frequency and intensity of heavy precipitation events are increasing globally and regionally with global warming [19][20][21]. The amount of daily precipitation could considerably alter evapotranspiration and runoff related to river discharges and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…2/3 of the land area of the Northern Hemisphere has experienced enhanced extreme precipitation, and multi‐model simulations of precipitation response to anthropogenic forcing are consistent with changes in terrestrial extreme precipitation observed in the Northern Hemisphere (Min et al, 2011; Zhang et al, 2013). The more extreme the precipitation event, the clearer the anthropogenic influence (Wang et al, 2023). The human influence dominated by the GHG effect has intensified extreme precipitation, especially in continental and regional extreme precipitation (Chen & Sun, 2017; Dong et al, 2021; Kirchmeier‐Young & Zhang, 2020; Sun et al, 2021; Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%